Precise Personalized Medicine in Gynecology Cancer and Infertility - Zhang, Pu-Yao; Yu, Yang (Frontiers in Cell and Developmental Biology, 2020)
Since the conception of precise medicine has been put forward in oncology, this idea has been popularized and applied in many specialties. Significant progress has been made towards personalizing the entire process, including diagnosis, treatment planning and embryo identification, and combining large-scale genetic information data and knowledge discovery can offer better prospects in reproductive medicine. This work reviews the application of precise medicine and possibilities in reproductive medicine and genecology cancer diagnosis and treatment. The limitations and challenges remain to be discussed.